Análise literária e iconográfica do Vampiro em A Condessa Sangrenta, de Alejandra Pizarnik - Souza, Izavanna Mota de (2018)
This research proposes to lecture about the vampire figure in A Condessa Sangrenta , by Alejandra Pizarnik. To do so, a folkloric study of the vampire myth is necessary, permeating historical figures and their influences, as well as historical vampiric accounts, in the transition from the folk to the literary figure. To base the study, the dialogue with the researches of Raymond Mcnally and Radu Florescu in his famous works Dracula myth or reality? and In Search of Dracula and other vampires will aid in the making of the folk panorama that this creature is inserted. The vampire, when migrating from folklore to literature, underwent transformations; his social actions acquire philosophical problems and the character acquires aesthetic innovation. The vampire is humanized but still endowed with alienism and alienation from society. The nocturnal creature is starring in Alejandra Pizarnik's A Condessa sangrenta (1967), a work inspired directly in the biographical essay of Valentine Penrose, The Blood Countess , both narratives based on the crimes of Erzsébeth Báthory, Countess Dracula, explored throughout the research . Published in Brazil in 2011 by the Tordesilhas, A Condessa sangrenta is illustrated by Santiago Caruso, an Argentine artist, influenced by symbolist and surrealist art, linked to the obscure elements. Thus, the analysis is at least dual; both text and illustration are the subject of research. The meeting of these two aristocratic figures, given to Penrose and Pizarnik, impresses traits pertinent to the vampire; the seduction, the dream, the love for beauty, the eternity and the challenge between the limits of life and death. Keywords: Literature, Iconography, Alejandra Pizarnik, Vampires, Elizabeth Bathory, Santiago Caruso.